Korrosionsbeständige mikroverfahrenstechnische Apparate durch CVD‐Beschichtung mit Tantal. Issue 8 (5th July 2018) - Gietzelt, Thomas; Kraut, Manfred; Messerschmidt, Florian; Fürbeth, Wolfram; Dittmeyer, Roland
Abstract: The wall thickness of microprocess apparatuses is not comparable to those of stirred vessels used in chemical industries. Already changes of the composition of corrosion resistant alloys in the range of the specification may cause severe deviations of the corrosion rate. Ideally, for micro process apparatuses, completely suppression of corrosion should be accomplished. Therefore, tantalum is the material of choice due to its superior corrosion resistance. It is demonstrated that microchannels possessing a small cross section but large length could be homogeneous coated with tantalum by means of a CVD process without any defects. Corrosion tests in 70 % sulfuric acid proved that no loss of weight or corrosion occurred.